Infantile-onset inflammatory bowel disease has variable long-term outcomes - Krauthammer, Alex; Weintraub, Ilana; Shaoul, Ron; Lev-Tzion, Raffi; Broide, Efrat; Wilschanski, Michael; Lerner, Aaron; Yerushalmi, Baruch; Shouval, Dror S.; Shamaly, Hussein; Haberman-Ziv, Yael; Weiss, Batia (Frontiers in Pediatrics, 2023)
Objective and Aim: Infantile-onset inflammatory bowel disease (IO-IBD), defined as IBD diagnosed at age 2 years or younger, tends to be more severe and refractory to conventional treatment than IBD diagnosed at a later age. However, data about IO-IBD and its long-term follow up are limited. We thus aimed to evaluate the presentation and long-term outcomes of patients with IO-IBD in a retrospective multicenter study. Methods: Medical records of patients diagnosed with IO-IBD in eight medical centers during 2000-2017 with at least 1-year follow up were reviewed. Demographics and disease characteristics at diagnosis including age of onset, disease phenotype and location, surgeries, medical therapy, and comorbid conditions were recorded. Results: Twenty-three patients with IO-IBD (16 males, 70%) were identified and followed for a median (range) of 51.2 (26.0-110.3) months. The mean ages at presentation and at the last follow up were 14±9.8 and 101±77 months, respectively. Six (26%) patients needed ileostomy already at the time of diagnosis and 20 (87%) were treated with corticosteroids. During long-term follow up, remission was achieved in 16 (73%) patients; of whom, 3 (14%) were without medications and 7 (32%) were in remission with the use of 5-aminosalicylic acid only. One patient needed hemicolectomy and one developed a severe EBV related infection. Conclusions: The majority of patients with IO-IBD achieved long-term remission, despite a severe disease presentation at diagnosis. Surgery rate however is high, mainly during the first months from diagnosis.